2019
DOI: 10.1108/lhs-06-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among authentic leadership, manager incivility and trust in the manager

Abstract: Purpose This study aims to examine the relationships among authentic leadership of managers and new graduate nurses’ (NGNs) experience of manager incivility and their degree of trust in their managers. Design/methodology/approach A secondary analysis of data using a non-experimental, correlational design was undertaken. From 2012 to 2013, 3,743 surveys were mailed to NGNs eligible for the study, and 1,020 returned completed questionnaires for a response rate of 27.3 per cent. The hypotheses were tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…Next to this, researcher has confirmed the relationship between psychological empowerment and employee creativity which is in line with Spreitzer (2008). Similarly, trust in leadership has confirmed positive impact on employee creativity and consistent with previous findings Alkaabi and Wong (2019) This study contribute to body of knowledge and investigated the moderating role of employee proactivity between employee creativity and perceived organizational performance. The moderating relationship is confirmed in such a way that it strengthens the relationship between employee creativity and perceived organizational performance and confirmed that the relationship between perceived organizational performance and employee creativity will be robust when employee proactivity is higher.…”
Section: Fig4 Interaction For Moderating Effect 5 Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Next to this, researcher has confirmed the relationship between psychological empowerment and employee creativity which is in line with Spreitzer (2008). Similarly, trust in leadership has confirmed positive impact on employee creativity and consistent with previous findings Alkaabi and Wong (2019) This study contribute to body of knowledge and investigated the moderating role of employee proactivity between employee creativity and perceived organizational performance. The moderating relationship is confirmed in such a way that it strengthens the relationship between employee creativity and perceived organizational performance and confirmed that the relationship between perceived organizational performance and employee creativity will be robust when employee proactivity is higher.…”
Section: Fig4 Interaction For Moderating Effect 5 Discussionsupporting
confidence: 87%
“…According to Jain et al (2019) the relationship between trustworthy leader and subordinates can be achieved through integrity, honesty and moral leadership standard. These attributes brings positive expectation among employees and enhance their willingness to accomplish organizational goal (Alkaabi & Wong, 2019). Another study conducted by Laschinger et al (2012) revealed that an authentic leader increase trust in subordinate which in turn enhance confidence in followers and help them to achieve firm goals.…”
Section: Trust In Leadershipmentioning
confidence: 96%
See 1 more Smart Citation
“…Secondly, the empirical evidence of the link between positive leadership and workplace incivility is somewhat limited [50]. Specifically, the previous literature on leadership, which examined its effects on workplace incivility, focused on many different forms or styles of leadership, such as passive leadership [25], transformational leadership [26], authentic leadership [5,27], but not positive leadership. Thus, our results showing the negative effect of positive leadership on workplace rudeness (i.e., workplace incivility) provide a theoretical contribution to the field of leadership.…”
Section: Discussion: Positive Emotion Positive Leadership and Open Innovationmentioning
confidence: 99%
“…Specifically, given that studies such as those by Rhee, Hur, and Kim [23], and Woo and Kim [24], have provided somewhat limited empirical evidence of the link between compassion and workplace incivility, this present study contributes to the compassion literature by unboxing the unknown processes of how compassion could lessen employees' rudeness at work. In addition, whereas leadership researchers have empirically explored the link between many different types of leadership style [25][26][27], we still do not know how positive leadership affects incivility at work. Hence, this current study also provides contributions to the leadership literature.…”
Section: Introductionmentioning
confidence: 99%